PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) BERBASIS APLIKASI BIOURINE SAPI - Tandi, Olvie G.; Paulus, J.; Pinaria, A. (EUGENIA, 2015)
ABSTRACT The research aims to assess the response to the growth and production of onion against of liquid organic fertilizer from cow biourie in some concentrations and to get the best concentration for the growth and production of red onion. The research was conducted atfield experimental in Pandu, North Minahasa regency from May to July 2014. The experiment was designed using a randomized block design. The treatment was concentration of cow biourine namely 0% (B1) 10%, (B2) 20%, (B3) 30%, (B4) 40% and (B5) 50%. Each treatment was replicated three times. Characters observed were plant height, number of leaves, tuber diameter, number of tuber, fresh weight of tuber with leaves and dry weight of tuber. Data was analyzed using analysis of variance. The result showed that the biourine concentration had significant effect on plant height, number of leaves, tuber diameter, number of tuber, fresh weight of tuber with leaves and dry weight of tuber. Treatment of B1, B2, B3 and B4 concentration were not significant difference at plant height. However, those four treatments were significantly different compared to B0 and B5. The fives treatment differed with the control on characters of number of leaves, number of tuber andfresh weight of tuber with leaves. On character of tuber dry weight, B2 treatment was significant difference compared to control whereas the other treatments were not significantly differed. On character of tuber diameter, three treatments were significant difference compared to the control namely B2, B4 and B5. Keywords : Allium ascalonicum L, biourine cow, fertilizer, growth and production